Global Mobility Management in Next Generation Networks - Sofia, Rute C. (2020)
Handling mobility management in the Internet is not trivial, given the heterogeneity of devices involved; providers involved; service requirements. The Internet evolution requires re-thinking mobility management and to understand how to best distribute functionality across the network. The contributions of this book to research in the field concern the evolutionary design of mobility management architectures and protocols; the debate on approaches such as mobility estimation or decoupling of mobility management functions. The book starts with today’s centralized approaches, going over the evolution towards de-centralization and distribution of mobility management, and finishes with an explanation on information-centric support. In comparison to state of the art, the book introduces concepts and examples that help to re-think mobility management in a way that is better suited for an Internet of the future. The key findings of these book are four-fold. Firstly, it introduces a debate on mobility management functions, based on different solutions for the TCP/IP stack. Secondly, it brings in a fresh look into decoupling of mobility management functions; thirdly, it brings awareness to the need to introduce mobility estimation as a relevant function of global mobility management. Fourthly, it addresses mobility management from the perspective of an information and service-centric Internet .